2017
DOI: 10.1007/s10753-017-0608-3
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Exogenous Melatonin After the Onset of Systemic Inflammation Is Hardly Beneficial

Abstract: Melatonin improves survival and functional impairment including hemolysis, thrombocytopenia, and hypotension when administered in a prophylactic manner or early after initiation of sepsis or endotoxemia. In the present study, melatonin was given not before first symptoms of systemic inflammation became manifest. Lipopolysaccharide was infused at a rate of 0.5 mg/kg × h to induce systemic inflammation in male Wistar rats. Melatonin (single dose 3 mg/kg × 15 min) was intravenously administered 180 and 270 min af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…In accordance with our findings, prophylactic treatment with melatonin has been reported to depress the TLR4/MyD88 pathway and protect neurons from focal cerebral ischemia or chloranil‐induced inflammation injury . Furthermore, pharmacological evidence also indicated that melatonin is highly efficient in minimizing tissue damage and preventing systemic inflammation only when administered in a prophylactic manner or soon after the injury . As the efficacy of prophylactic melatonin treatment is more evident than that of treatment after the induction of PD, the present study not only highlights the functional roles of melatonin in the treatment of PD, but also provides a critical insight for clinical use of melatonin as a preventive strategy to effectively repress PD‐induced destructive injury.…”
Section: Discussionsupporting
confidence: 88%
“…In accordance with our findings, prophylactic treatment with melatonin has been reported to depress the TLR4/MyD88 pathway and protect neurons from focal cerebral ischemia or chloranil‐induced inflammation injury . Furthermore, pharmacological evidence also indicated that melatonin is highly efficient in minimizing tissue damage and preventing systemic inflammation only when administered in a prophylactic manner or soon after the injury . As the efficacy of prophylactic melatonin treatment is more evident than that of treatment after the induction of PD, the present study not only highlights the functional roles of melatonin in the treatment of PD, but also provides a critical insight for clinical use of melatonin as a preventive strategy to effectively repress PD‐induced destructive injury.…”
Section: Discussionsupporting
confidence: 88%
“…Melatonin has been shown to have beneficial effects in the treatment of sepsis and inflammation (22, 23, 30, 43, 44). Treatment with melatonin contributed to the inhibition of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) and NACHT, LRR, and PYD domain-containing protein 3 (NLRP3) pathway, which are essential components of inflammasomes (45).…”
Section: Discussionmentioning
confidence: 99%
“… 9 12 The experimental model of continuous LPS infusion used in the present study reflects most pathophysiological changes known from clinical severe sepsis. 30 , 33 , 34 So, continuous infusion of LPS in our model led to an early hyperglycemic pre-shock state followed by a later hypoglycemic shock state. It induced severe functional impairment and tissue injury.…”
Section: Discussionmentioning
confidence: 74%